Condition of Metal-Ceramic Restorations after Five Years in Function: A Cross-Sectional Evaluation - Hasham Khan, Yasir Hussain, Aamir Syed, Sanam Afridi, Khola Aziz Uddin, Sajida Sabir (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To assess the clinical condition and complications associated with metal-ceramic restorations (MCRs) after five years in function. Materials and Methods: A cross-sectional evaluation was conducted the Department of Prosthodontics Kohat from January 2022 to December 2022, among patients who had MCRs placed five or more years previously. Restorations were clinically evaluated for marginal integrity, colour match, porcelain chipping, occlusal wear, and periodontal responses using modified USPHS criteria. Patient hygiene status and occlusal factors were also recorded. Results: A total of 124 restorations in 73 patients were examined. Marginal integrity was rated clinically acceptable in 92.7% of restorations. Minor porcelain chipping was found in 14.5%, while major chipping requiring repair occurred in 5.6%. Colour match was rated satisfactory in 86.3%. Gingival inflammation was observed in 25.8%, primarily in patients with inadequate plaque control. Conclusion: Metal-ceramic restorations show high survival and functional stability after five years. The most common complications observed were porcelain chipping and mild periodontal inflammation. Regular follow-up and maintenance care can reduce biological complications. Keywords: Metal-ceramic restorations, porcelain chipping, marginal integrity, periodontal status.